Water Quality Control and Monitoring at The Patih Drinking Water Depot Based on Nodemcu ESP32 - St. Nurhayati Jabir; Asyraful Insan Asry; Rahmat Hidayat (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2024)
Manual control and monitoring of water quality remain a significant challenge for managers of drinking water depots, potentially affecting water safety and operational efficiency. To address this, an automated system was developed to fill water tanks and monitor water quality using advanced sensors and a real-time notification system. The solution integrates a Node MCU ESP32 microcontroller, a pH sensor for detecting water acidity, a TDS sensor for dissolved solids, an ultrasonic sensor for water level detection, and a Telegram bot for remote monitoring and notifications. The system activates the pump under optimal conditions pH between 6.5 and 8.5, TDS below 150 ppm, and water level below 30 cm and deactivates it when conditions deviate, such as pH outside the range, TDS exceeding 150 ppm, or water level reaching 120 cm. Notifications on pump status, pH, TDS, and water levels are sent via Telegram. Testing demonstrated reliable operation, with the system correctly activating and deactivating the pump under specified conditions, enhancing water quality management and operational effectiveness in drinking water depots.